Reevaluation of the role of duration of morning stiffness in the assessment of rheumatoid arthritis activity. - Khan, N; Yazici, Y; Calvo-Alen, J; Dadoniene, J; Gossec, L; Hansen, T; Huisman, M; Kallikorm, R; Muller, R; Liveborn, M; Oding, R; Luchikhina, E; et al. (2009)
OBJECTIVE: To evaluate the utility of the duration of morning stiffness (MS), as a patient-reported outcome (PRO), in assessing rheumatoid arthritis (RA) disease activity. METHODS: We acquired information on 5439 patients in QUEST-RA, an international database of patients with RA evaluated by a standard protocol. MS duration was assessed from time of waking to time of maximal improvement. Ability of MS duration to differentiate RA activity states, based on Disease Activity Score (DAS)28, was assessed by analysis of variance; and a receiver-operating characteristic (ROC) curve was plotted for discriminating clinically active (DAS28 > 3.2) from less active (DAS28 <or= (95%="" (<="" (ancova)="" (das28v3="" (das28v3).="" (gh),="" (p="0.0005)" (r="0.23-0.39)" (rapid)3,="" 0.001).="" 0.72-0.75)="" 0.74="" 3-variable="" 3.2)="" 6)="" <="" a="" ability="" active="" activity="" adding="" among="" analysis="" ancova="" and="" area="" assess="" assessment="" based="" be="" between="" categories="" ci="" clinically="" correlation="" counts="" covariance="" curve="" das28="" das28v3.="" data="" differed="" different="" differentiate="" disease="" duration="" effect="" effects="" erythrocyte="" found="" from="" function,="" general="" gh;="" had="" health="" important="" in="" index="" indicate="" interactive="" joint="" less="" low="" may="" mixed-effect="" models="" moderate="" ms="" of="" on="" pain,="" patient="" patients="" physical="" predicting="" presence="" pro="" questionnaire,="" ra="" ra.="" rapid3="" rate.="" results:="" roc="" routine="" scores="" sedimentation="" showed="" significant="" significantly="" the="" to="" under="" used="" utility="" was="" weak="" were="" whom="" with=""> 3.2). CONCLUSION: MS duration has a moderate correlation with RA disease activity. Assessment of MS duration may be clinically helpful in patients with low RAPID3 scores.</or=>